MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: R

There are no items in this cart.
Continue Shopping
Menu
paradox xyz cool Grade: 11
        

prove that:


sin2(n + 1)A - sin2nA = sin(2n + 1)A.sinA

6 years ago

Answers : (2)

vikas askiitian expert
510 Points
										

sin2(n+1)A - sin2nA = sin(2n+1)A.sinA


we have formula sin2a - sin2b =sin(a-b)sin(a+b)


therefore


                 sin2(n+1)A - sin2nA=sin[(n+1)A+nA].sin[(n+1)A-nA]


                                            =sin(2n+1)A.sinA =RHS


hence proved

6 years ago
madhu voleti
44 Points
										

sin^2(n + 1)A - sin^2nA = sin(2n + 1)A.sinA
Solution:-
    L.H.S:-sin^2(n + 1)A - sin^2nA =
        Sin[(n+1)A+nA].Sin[(n+1)A-nA]        ["a^2-b^2=(a+b)(a-b)"]
        =Sin[nA+A+nA].Sin[nA+A-nA]
        =Sin[A(n+1+n)].SinA
        =Sin(2n+1)A.SinA=R.H.S


 


Thank You!!!!!!!!!!!!!!!!


Wish You Happy learning of trignometry..............

6 years ago
Think You Can Provide A Better Answer ?
Answer & Earn Cool Goodies
  • Complete JEE Main/Advanced Course and Test Series
  • OFFERED PRICE: R 15,000
  • View Details

Ask Experts

Have any Question? Ask Experts

Post Question

 
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!! Click Here for details